Are sukuk really giving return? Evidence from the Malaysian market / Mukhairi Ibrahim, Ibrahim Hanif Md. Ghazali & Suria Haryati Mohamed Ali - Ibrahim, Mukhairi; Md. Ghazali, Ibrahim Hanif; Mohamed Ali, Suria Haryati (2013)
Last decade has witnessed rapid expansion of Islamic financial instruments with particularly the increase of Islamic investment certificates called Sukuk. Since Sukuk represent an alternative instrument to conventional bonds, it is of interest to evaluate the economic differences between these financing techniques and appraise the implications on the future expand of Sukuk. Performance analysis is use to investigate whether sukuk is under performing compare to conventional bond. This study found that the market perceived the risks of the instruments (Sukuk and Conventional bond) as the same that is why the return of the financial instrument is not significantly difference. For the issuer of Government Sukuk and on Government Sukuk the finding revealed, the risk are different event though based on same instrument (Sukuk), that is why the return of the issuer are significantly difference. For the on Government based Sukuk gave more return compare to Government Sukuk. The market perceived the risks of the two instruments (Sukuk and Conventional Bond) for government and non government issued as the same, that is why the return of the financial instrument for Government or Non Government based Sukuk or Conventional issued is not significantly difference.